Module Development on Basic Laws of Chemistry Based on the 5E Instructional Model to Improve Science Process Skills in Senior High School - Fitrah Mey Harmi Siregar; Rahadian Zainul; Andromeda; Budhi Oktavia; Amalia Putri Lubis (Jurnal Penelitian Pendidikan IPA, 2023)
The module is one of the teaching materials that is arranged as a whole and systematically. Modules based on learning models can change learning patterns from teacher center to student center. One of the learning models developed specifically for subject matter in the field of science is 5E instructional. The 5E Instructional Model consists of 5 stages namely engagement, exploration, explanation, elaboration and evaluation. The purpose of this study was to develop an instructional module based on 5E chemical laws to improve the process skills of science students. The type of research conducted is research & development (R&D) with the ADDIE development model. The results obtained for the validity of the construct and content were 0.89 and 0.91 with the valid category. Based on the results of the teacher and student response questionnaires, an average practicality score of 86.96% and 86.10% was obtained in the very practical category. The results of the effectiveness test conducted in the experimental and control classes showed that the N-gain value for the experimental class was higher than the control class, namely 0.84 and 0.79. Based on the results of the t-test on student learning outcomes, it was found that tt < th means that the learning outcomes of classes using the 5E instructional module were significantly higher compared to classes that did not use the 5E instructional module. Therefore, it can be said that the 5E-based basic chemistry law module is valid, practical, and effective. The effectiveness of the developed module is seen from the learning outcomes of students and science process skills, so that this module can already be used in the learning process.